Potential E Business in International SMEs (Study of UKM Raragu Craft in Pasuruan) - Munandar Munandar; Sudarmiatin Sudarmiatin; Imam Mukhlis (International Journal of Economics, Business and Innovation Research, 2023)
Internet technology has brought great changes to the way of doing business today. Many terms have been coined to represent electronic concepts and applications such as e-Business and eCommerce. These terms are usually used to represent the transformation of business processes and transactions. In Pasuruan, the adoption of e-business has not only attracted the interest of large organizations but has also been recognized and adopted by small, medium and micro enterprises. Implementing e-Business requires significant changes in corporate structure, culture, strategy, procedures and responsibilities. However, those challenges have not stopped people from venturing into this new business concept. A study was conducted to see the potential of e-business for micro-scale businesses conducted by UKM Raragu Craft in Pasuruan. In this study used qualitative methods. This article reviews issues related to e-business and business education, describes the methodology and reports preliminary findings from the research.